Evaluation of the Small Changes, Healthy Habits Pilot Program: Its Influence on Healthy Eating and Physical Activity Behaviors of Adults in Louisiana - Praja Adhikari; Elizabeth Gollub (MDPI AG, 2021)
The community-based Small Changes, Healthy Habits (SCHH) program was developed to teach skills and techniques to help adults in Louisiana make and maintain small behavioral changes in their food selection, preparation, and consumption, and in physical activity routines. The content of this four-week program included habit formation and goal setting techniques; physical activity guidance; strategies for a healthier home food environment; a grocery store tour focused on label reading for healthier food selections; basic knife and cooking skills. The program was piloted at ten sites throughout the state. A survey with 14 core items was applied before and after the program to evaluate participant acquisition of skills and behaviors associated with topic areas. A total of 47 participants provided complete data sets. Post-program, these participants reported increased confidence in preparing healthy meals at home (p = 0.04); changes in fats (p = 0.03) and salt (p = 0.01) intake; increased frequency of reading nutrition labels (32%); decreased frequency of meals eaten outside the home (Improvement Index = 0.27); and decreased time/day spent sitting (p < 0.05). These short-term results suggest that the SCHH program has potential to positively affect healthy eating and to reduce sedentary behaviors, both of which are fundamental to good health and wellness.